Multi-Spacecraft Observations of Fluctuations Occurring Along the Dusk Flank Magnetopause, and Testing the Connection to an Observed Ionospheric Bead - Petrinec, Steven M.; Wing, Simon; Johnson, Jay R.; Zhang, Yongliang (Frontiers in Astronomy and Space Sciences, 2022)
During 2018 November 06, 11:30 – 18:00 UT, the MMS constellation, the Cluster set of spacecraft, and the Geotail spacecraft were all situated near the dusk flank magnetopause. Large scale fluctuations were observed by the available and operating science instruments at these various spacecraft (i.e., magnetic field, plasma moment, and energy flux measurements). Similar fluctuations were not observed by upstream solar wind monitors, suggesting that the waves were initiated at the magnetopause. A localized emission ‘bead’ from the post-noon ionosphere were also observed from low Earth orbit. The nature and relation of the fluctuations observed at all of these spacecraft at the magnetosphere boundary and the connection to the post-noon high-latitude ionosphere are investigated in this study.